2007
DOI: 10.1088/0029-5515/47/9/019
|View full text |Cite
|
Sign up to set email alerts
|

Microturbulent drift mode suppression as a trigger mechanism for internal transport barriers on Alcator C-Mod

Abstract: Internal transport barriers (ITBs) can be routinely produced in enhanced D  (EDA) H-mode discharges on the Alcator C-Mod tokamak by putting the minority ion cyclotron resonance layer at |r/a| ≥ 0.5 during the current flat top phase of the discharge. These ITBs are characterized by density peaking at constant temperature, and are therefore both particle and energy transport barriers. The ITB formation appears to results from widening the region near the magnetic axis in which toroidal drift modes are stable, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…First, the off-axis heating reduces the temperature profile gradient, and thus the drive for ITG instabilities. 256,258 However, by itself, this mechanism is not strong enough to suppress the instability and account for barrier formation. The second ingredient, E Â B stabilization, arises because of changes in the rotation profile that occur when the RF heating resonance is positioned offaxis.…”
Section: à3mentioning
confidence: 99%
“…First, the off-axis heating reduces the temperature profile gradient, and thus the drive for ITG instabilities. 256,258 However, by itself, this mechanism is not strong enough to suppress the instability and account for barrier formation. The second ingredient, E Â B stabilization, arises because of changes in the rotation profile that occur when the RF heating resonance is positioned offaxis.…”
Section: à3mentioning
confidence: 99%
“…Further analysis was done by Zhurovich et al [28] on plasmas that were part of a magnetic field scan, i.e. the ICRF resonance was moved shot by shot until ITBs began to form in the H-mode phase of the plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Redi et al [27] concluded that the ion temperature profile that occurs with offaxis heating is broad enough to reduce the ITG drive term that dominates the transport in these high density plasmas. The work of Zhurovich et al [28] supported this conclusion and demonstrated how the change in the ICRF resonance position affects the ion temperature profiles and the resulting turbulence driven flux. Zhurovich was also able to demonstrate with the gyrokinetic modelling that the small magnetic shear found in the core region of Alcator C-Mod was not significant in suppressing the ITG instability in these plasmas.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Promising results along these lines are related to the formation of narrow regions in the core of fusion devices with reduced turbulent transport, commonly called internal transport barriers (ITBs) [1] (and reference therein). Internal transport barriers have been widely observed in magnetic confinement devices under different experimental conditions in both tokamaks and stellarators [2][3][4][5][6][7][8][9][10][11][12][13][14]. Their formation is typically associated with nearly flat or reversed shear configurations s = ρ/q (dq/dρ) < 0 (with q safety factor and ρ the radial coordinate) [15][16][17], MHD activity in proximity of low-integer rational surfaces in the safety factor [18,19] and fast ion effects in highly electromagnetic regimes [20,21].…”
Section: Introductionmentioning
confidence: 99%